PENINGKATAN PEMAHAMAN MENGENAI DESAIN LABEL DAN KEMASAN PADA PRODUK OLEH-OLEH DI DESA WIDARAPAYUNG WETAN KABUPATEN CILACAP - Ayu Pramita; Oman Somantri; Oto Prasadi; Theresia Evila Purwanti Sri Rahayu; Nurlinda Ayu Triwuri; Ilma Fadlilah (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
The number of Micro, Small and Medium Enterprises (MSMEs) in Indonesia as of September 2021 reached 64.2 million by contributing a GDP of around 61.07 percent and being able to absorb 97% of the total existing workforce, and was able to collect 60.42% of the total investment in Indonesia. This indicates that MSMEs have great potential to be developed, besides that MSMEs also contribute gross domestic product (GDP) in Indonesia, open opportunities to empower family finances, open business opportunities and absorb labor which in turn can improve the economy in Indonesia. However, the last two, the whole world has experienced economic paralysis caused by the Covid-19 pandemic outbreak, as well as what happened in Indonesia. One of them has experienced a bad impact on MSMEs/ MSEs. The product of various chips